Examining short-term rentals' influence on tourists' well-being using Airbnb reviews - Lupu, C. (2023)
Smart tourism innovations are changing tourism. Tourists are increasingly demanding more authentic experiences and non-traditional accommodations (e.g., Airbnb) that offer closer connections to hosts and locals. Airbnb presents lodgings ranging from shared rooms and apartments to treehouses. Peer-to-peer accommodations create value for customers via reasonable prices, flexibility, ease of use, and local-guest interactive communication. Smart tourism has facilitated this new business ecosystem’s development within the sharing economy. This study sought to examine guests’ experiences in Bucharest Airbnb apartments and the main themes associated with these tourists’ subjective well-being. The sample of 750 online reviews were analysed using Leximancer, which revealed five themes—apartment, stay, old, host, and nice (view)— and their positive outcomes—recommend(ation), thank you(s), and value (for money). The results reveal that hosts’ friendliness contributes the most to guests’ affective wellbeing, which has theoretical and practical implications for Romania’s tourism industry.